Strengthening Islamic Financial Literacy through Product Innovation in The Era of Globalization: A Qualitative Literature Study from The Perspective of Islamic Economics - Dimas Fadilah; Ma’mur Munajat; Azizan Sentosah Hutabarat (Sekolah Tinggi Agama Islam Kuningan, 2025)
This new era of digital connectivity has made information more accessible, but also highlighted challenges such as disparities in digital literacy and access to technological resources. In Indonesia, the gap in Islamic financial literacy remains a significant barrier to the optimal growth of the Islamic financial industry. Despite increasing access to information, understanding of Islamic financial products remains low. Amidst globalization and the overwhelming flow of information, product innovation is crucial for enhancing public interest and knowledge of Islamic financial services. These innovations include product simplification, the integration of digital technology, and the incorporation of Islamic values into product design and promotion. This study aims to examine the strategy of strengthening Islamic financial literacy through product innovation in response to the challenges of the globalization era, using a qualitative literature review approach from an Islamic economic perspective. The findings indicate that the low level of Islamic financial literacy in Indonesia remains a significant obstacle to the optimal development of the Islamic financial industry. In the context of globalization, product innovation is crucial to increasing the attractiveness and public understanding of Islamic financial services. This research also emphasizes the importance of the role of Islamic financial institutions, the government, and relevant authorities in providing sustainable, collaborative education based on Islamic values. Strengthening Islamic financial literacy will promote public participation in the Islamic financial system and enhance the economic resilience of the ummah both nationally and globally.